(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses in detail the environmental problems in Kyrgyzstan. The authors have proposed materials and technologies to solve some of them. The magnetically controlled nanocomposite materials developed by them possess the properties of both highly effective sorbents and specific properties of magnetic materials.